Consumption of Public Childcare and Educational Services: an End-User Perspective - Speranţa Pirciog; Aniela Matei; Bertha Sănduleasa; Mihaela Ghenţa (Amfiteatru Economic Journal, 2010)
Public childcare and educational services are complex services resulting in a relationship that is established between a supplier and a consumer of such services. In 2002 the European Council meeting in Barcelona, established that by 2010, the Member States should develop childcare services for at least 90% of children between 3 years old and the mandatory school age. This will stimulate the consumption of public services for the care and education of children. This article aims to analyze the consumption of public childcare and educational services in Romanian kindergartens. The first part provides conceptual clarification on consumption and consumers of public childcare and educational services and the second part assessed the rights of children and parents to such services. The last part presents some of the results of a questionnaire based exploratory survey conducted in Bucharest on the quality of services provided in preschool education from the perspective of users: parents of preschool children. The results show that the existence of legal regulations in the field, the access to quality services and the cost of these services represent key elements to determine the consumption of such services.
Keywords: I21; H4; 330; public services; childcare and educational services in kindergartens; consume⁲ s rights; public childcare and educational services consumption